Development of multi-use platforms at sea: Barriers to realising Blue Growth. (1st December 2020) - van den Burg, S.W.K.; Schupp, Maximilian Felix; Depellegrin, Daniel; Barbanti, Andrea; Kerr, Sandy
Abstract: The recent H2020 Blue Growth projects MARIBE and MUSES investigated the potential of a variety of different combinations of economic activities in co-location or integrated in multi-use platforms. Both projects identified barriers - including regulatory, financing, liability and insurance issues; environmental concerns; stakeholder perceptions; and lack of appropriate skills – that hamper the development of multi-use platforms. The H2020 MARIBE project concluded that further funding for multi-use demonstrations should be provided to increase investor confidence and bring multi-use through the so-called Valley of Death. The H2020 MUSES project concluded that multi-use needs to be proactively facilitated and incentivised through public regulatory bodies and respective support programmes. This paper combines and analyses results from both projects in order to identify key research gaps and actions required for the continued development of multi-use platforms, based on a structured critical review of available peer-reviewed literature on the topic as well as reports of both the MUSES and MARIBE projects. Research gaps and actions are analysed based on a multi-use platform typology to inform developers, policy makers, academia and investors for future development of multi-use at sea. Highlights: A review of key EU funded research projects into multi-use platforms (MUPs). A unified classification system for MUPs is presented. Gaps in current research into MUPs are identified. Technical and non-technical barriers to the implementation of MUPs are identified. Recommendations are made as to how barriers to the deployment of MUPs can be removed.